Viabilidade de uso do modelo IPH2 como ferramenta de apoio a gestão hídrica da sub-bacia hidrográfica do Rio Poxim-Açu, Sergipe - Rocha, Ricardo Monteiro (2014)
Historically the issue of sustainable development is gaining emphasis in government policy decisions. The supply of water is in a crisis. For decision making a thorough study of the watersheds of the country for better efficiency in the management of water resources is necessary. The motivation of this research is based on hydrologic modeling n as subsidy programs for water resources management and analysis of water availability in the study area. This work models the behavior of the flow in the river basin Poxim-Açu, in the state of Sergipe and has the overall objective to study the flow in the river basin Poxim-Açu through hydrologic modeling using the IPH2 model and specific objectives 2 Calibrate the model IPH2 for the basin studied and compare results with those conducted by Silva (2013). Performance analysis of the model after calibration was rated satisfactory by the literature. The model showed the following coefficients: NSE = 0.73, R ² = 0.74, PBIAS = -7.44, RMSE = 0.95, RSR = 0.07. These values, compared with the work of Silva (2013) have certain conformity. What endorses the model as suitable for the study of hydrological processes in the study area. The statistics worsened during validation we react to the calibration period, but even so the model can be considered acceptable for a larger sample of observed data flow.